Natural Radioactivity Measurements of Soil Samples from Al-Iraqia University New Location in North Baghdad - Raja, Waleed Nassar (Al-Nahrain Journal of Science, 2018)
Gamma ray spectroscopy technique with detector of high purity germanium (HPGe, 30% efficiency, energy separation 2.2keV at 1332keV for Co-60 isotope) connected to GINE-2000 program, has been used to measure the specific activity of ten soil samples taken from the new location of Al-Iraqia University 30 km north to Baghdad. Results have shown that the average specific activity of Pb-214, Bi-214 nuclides, as an equivalent to the U-238 specific activity is 15.4320.936 Bq/kg and 14.6541.33 Bq/kg for the (Ac-228, Ti-208) as an equivalent to the Th-232. On the other hand, the average specific activity of K-40 was 772.5300.87 Bq/Kg and (6.9520.79Bq/kg) for CS- 137 isotope. An agreement has been found between the present results and the allowable lower limit values considered by the IAEA for specific activity.